"Open Business" as an Effective Model of a Creative Cluster ("Journal "U". Economy. Management. Finance.", 2021)
The article is devoted to the peculiarities of the functioning of creative clusters. The article analyzes the "Open Business" business model and the possibility of its implementation in the system of creative clusters.
Keywords: creative cluster; business model; cluster formation; partner companies; cooperation